2005
DOI: 10.1051/0004-6361:20042327
|View full text |Cite
|
Sign up to set email alerts
|

Further experiments on collisional tribocharging of cosmic grains

Abstract: Abstract. We experimentally investigated tribocharging in bouncing dust grain collisions under conditions which are relevant for the early solar nebula. We used silica, diamond, graphite, and silicon carbide grains and cm-sized targets of aluminum, iron, and graphite. We varied particle size around 1 µm, collision velocity between 38 to 106 m s −1 , and target temperature between 240 K and 360 K. Generally, the grains acquire something in the order of hundreds or thousands of negative elementary charges, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 30 publications
2
23
0
Order By: Relevance
“…These processes altered the original packing densities of the constituent particles within these porous objects, as we discuss in more detail in x 6.2. proposed another mechanism for the growth beyond the fragmentation limit, based on electrostatic charging in mutual collisions. Poppe et al (2000b) and Poppe & Schräpler (2005) showed that mutual collisions among dust grains lead to an electrostatic charging of the collision partners. A succession of nonsticking collisions between a macroscopic dust agglomerate and smaller bodies in the solar nebula can cause an accumulation of charges on the larger body, whose electrical field close to the surface, as a consequence, grows in strength.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These processes altered the original packing densities of the constituent particles within these porous objects, as we discuss in more detail in x 6.2. proposed another mechanism for the growth beyond the fragmentation limit, based on electrostatic charging in mutual collisions. Poppe et al (2000b) and Poppe & Schräpler (2005) showed that mutual collisions among dust grains lead to an electrostatic charging of the collision partners. A succession of nonsticking collisions between a macroscopic dust agglomerate and smaller bodies in the solar nebula can cause an accumulation of charges on the larger body, whose electrical field close to the surface, as a consequence, grows in strength.…”
Section: Introductionmentioning
confidence: 99%
“…At some critical value for the field strength, the escaping fragments, on average oppositely charged to the protoplanetesimal, are no longer able to escape the attractive Coulomb potential and are therefore reattracted to the surface of the larger body. As the mean size of the protoplanetesimals grows, the mean collision velocity, and hence the number of electrostatic charges per unit projectile mass separated in a collision, also increases ( Poppe et al 2000b;Poppe & Schräpler 2005), so that the timescales for reaching the critical electrical field strength decreases. In contrast to the abovementioned ''aerodynamic'' accretion, we call this phenomenon ''electrostatic'' accretion.…”
Section: Introductionmentioning
confidence: 99%
“…Upon collision, a significant amount of charge is placed on each particle. More recent studies show that the charge of dust grains after collision depend on humidity, temperature, and its velocity [Poppe and Schrapler, 2005]. On the basis of the two tribocharging scenarios and the vertical charge transport similar to the thunderstorm precipitation electrification mechanism [Mathpal et al, 1980], Farrell et al [2003] developed a fully analytical electrodynamic model of a dust devil with simplified assumptions of dust devil structures, time rate of charging, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The simple model described by equations (1) and (2) has a functional form consistent with observations -smaller particles acquire net negative charge during collisions with larger particles, and the charge transfer increases with the relative difference in particle size. However, this model does not account explicitly for other variables that likely affect the charge transfer such as temperature, humidity (Guardiola et al, 1996) and particle speed (Poppe and Schrapler, 2005). Moreover, it assumes that particles get fully charged after a single collision.…”
Section: Charge Transfer In Colliding Dust/sand Particlesmentioning
confidence: 99%